Co-Creating Birth and Death on Social Media - Leaver, Tama (Routledge, 2018)
While social media are, by definition, about connecting multiple people, many discussions about social media platforms and practices presume that accounts and profiles are managed by individual users with the agency to make fully informed choices about their activities. When discussing children, especially younger children, their agency is at times characterized as partial, or emerging, but with the presumption that with sufficient time they will eventually reach the same (presumed) status and ability as adult users (Livingstone & Third, 2017). At the other end of life, at the moment of death, the social media traces and online presences that persist after a user has passed away also present challenges in terms of agency. While there is an increasing push to include some sort of instructions about digital property in wills, these instructions are currently few and far between. Some platforms have deployed algorithmic solutions which have begun to address the reality of deceased users, but these are, at best, partial and largely insufficient responses. With these two figures in mind, I argue that the very young—from conception to birth and early infancy—and the recently deceased both act as liminal figures where the question of their (lack of) agency on social media highlights some of the ongoing challenges in presuming that social media traces can always be the responsibility of users with full, or even partial, agency. Rather, using a range of examples, I argue in this chapter that more encompassing ways of thinking about the relationship between social media, networked selves, and identities are needed. Drawing on work from the creative industries, I suggest that the term “co-creation” can be reframed to emphasize the way in which social media almost always entail creating other people’s identities as much as our own. Parents and carers are the first arbiters and co-creators of a young person’s life, making a large number of important choices about what sort of private 36or public online presence a newly born baby will have, how that presence will develop over time, on which platforms, and under which circumstances. Parents, in effect, can choose to name their children into being online, and in doing so must navigate the parental joys of sharing whilst balancing this against the rights of the child to, amongst other things, privacy in the present and future. At the other end of life, but in functionally similar ways, the loved ones left behind by the recently deceased will often need to make decisions about which social media profiles and traces persist after that user has died, how these traces will be (re)framed, and what online spaces will persist (if any), possibly in the form of online memorials. Moreover, both ends of life are now situated in an online context where real identities and real names, which persist over time, are both expected and demanded by the policies and practices of online platforms. The use of real names on social media amplifies the impact and longevity of social media traces, whether early or late in life. In outlining the challenges inherent in framing the very young, and the recently deceased, online, I argue in this chapter that a broader sense of agency and impact is needed across all life-stages on social media. A wider lens in terms of the way users contribute to the stories of each other on social media may well assist us all in making decisions about online material that inevitably impact the lives and legacies of other people.